Milestones of History: Age of Optimism: (Vol.8) - Edited by Palmer, Alan (London The Readers Digest Association Ltd., 1974)
From the beginnings of Ancient Egypt to the first moonwalk, this is a large coffee-table type book that provides the history of the world told in 100 exciting key episodes with 1500 illustrations as well as maps and diagrams. Between articles there are two page spreads to fill the history outside of the 100 key events. Another help which I haven't seen elsewhere is timelines for each major epoch that show the overlapping life spans of rulers, thinkers, artists, etc. as correlated with key events. More recent attempts I have seen at this same approach do not seem as complete or satisfying. A great way to get yourself or a high-school aged child excited about history. They broke the mold when they made this book.
Includes Colored Illustrations and Index.
Keywords: World History